Exploration and mutagenesis of the germacrene A synthase from Solidago canadensis to enhance germacrene A production in E. coli - Jinyan Huo; Xiaohui Chu; Bo Hong; Ruo Lv; Xiaoyu Wang; Jianxu Li; Ge Jiang; Baomin Feng; Zongxia Yu (Synthetic and Systems Biotechnology)
β-elemene is an effective anti-cancer component which has been widely used in clinic. However, it still relies on the extraction from the Chinese medicine plant Curcuma wenyujin, which seriously limits its application. Synthetic biology offers a promising approach to satisfy its supply. β-elemene is derived from germacrene A (GA), which is synthesized by germacrene A synthase (GAS), through Cope rearrangement under heat condition instead of enzymatic reaction. In this study, an effective germacrene A synthase (ScGAS) was identified from Solidago canadensis which could produce GA when expressed in E. coli. By introducing the heterogeneous MVA pathway to enrich the FPP pool, the strain yielded 147 mg/L of GA in shake flasks which represented 2.98-fold improvement over the initial one. Moreover, combining molecular docking with phylogeny analysis of ScGAS largely narrowed down the category of its key residues' mutagenesis. The Y376L mutant showed the highest yield of 487 mg/L which was almost 10-fold higher than the initial yield. These results indicate that diverting the metabolism of the host and enzyme mutagenesis based on the combination of molecular docking and phylogeny analysis are of great value to constructing terpenoids chassis.